Experimental Investigation of the Use of Expansive Materials to Increase Permeability in Coal Seams through Expansive Fracturing. (31st July 2020) - Cui, Xiao; Zhang, Jiayong; Guo, Liwen; Gong, Xuemin
Abstract : Hydration reactions of expansive materials are typically very safe, easy to induce, and low in cost, while the crushing of such materials is typically free from noise, dust, vibration, and toxic gases. In the present study, to realize the application of expansive materials in the prevention of coal seam gas disasters, the microstructure, heat release rate, and expansive pressure of expansive materials were investigated for different degrees of hydration based on temperature and pressure measurements and using a scanning electron microscope (SEM); fracture characteristics were determined based on fracture tests of coal-like materials. The results show that the expansive material with +30% water has the lowest hydration temperature (100°C). The expansive pressure of the steel tube was found to reach 57 MPa, which is deemed suitable for application in coal seams. The strain and displacement of coal-like materials were found to increase with time, with four main cracks appearing. Based on these results, it is feasible that hydration reactions of expansive materials could increase both gas drainage and permeability in coal seams, thus reducing the risk of rock burst around boreholes in coal seams.